Pengaruh Kualitas Layanan terhadap Kepuasan Pengguna DANA Dalam Transaksi E-Commerce - Widya Hamzah (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of DANA e-wallet service quality on user satisfaction in e-commerce transactions, with ease of use as a mediating variable and digital literacy as a moderating variable. The study is motivated by the increasing adoption of e-wallet services in Indonesia, which has not been fully accompanied by optimal user satisfaction. A quantitative research approach was employed using a survey method involving 116 active DANA users who had conducted e-commerce transactions within the last three months. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The findings indicate that service quality has a significant effect on user satisfaction, both directly and indirectly through the mediating role of ease of use. Furthermore, digital literacy significantly moderates the relationship between service quality and user satisfaction. These findings highlight the importance of improving service quality, enhancing ease of use, and strengthening digital literacy to improve user experience and satisfaction in digital payment transactions. This study contributes theoretically to the development of technology acceptance models and provides practical implications for e-wallet service providers and e-commerce businesses in Indonesia.